Peningkatan Hasil Belajar IPS Pada Konsep Peta Lingkungan Siswa MI Banjar - Zainuddin, M. (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to describe and analyze the social studies learning process using the concept of environmental maps for class IV students of MIN 11 Banjar. The research adopts a classroom action research approach conducted collaboratively between teachers and supervisors. The research subjects consist of 13 students from class IV of MIN 11 Banjar. The data collection methods employed in this study include interviews, observations, and tests. The research is conducted in two cycles: cycle 1 and cycle 2. The results indicate that the implementation of the concept of environmental maps in social studies learning has a positive impact on learning outcomes. The initial assessment conducted prior to the research implementation reveals a noticeable improvement in the learning outcomes after the utilization of environmental maps. Environmental maps serve as effective teaching tools in social studies, providing visual representations of the relationships between geographical features, human activities, and their impact on the environment. Through the utilization of these maps, students are able to develop a deeper understanding of the subject matter and establish connections between various elements in their surroundings. The concept of environmental maps encourages students to explore and analyze their local environment, nurturing a sense of place and fostering critical thinking skills. By engaging in interactive discussions and hands-on activities, students become active participants in the learning process, resulting in increased engagement and enhanced learning outcomes. Moreover, the collaborative nature of this research, involving both teachers and supervisors, contributes to the quality of the learning environment. The close cooperation between educators facilitates the sharing of knowledge, expertise, and instructional strategies, ultimately benefiting the students' learning experience. In conclusion, this study highlights the positive effects of integrating environmental maps in social studies learning for class IV students of MIN 11 Banjar. The utilization of environmental maps significantly enhances learning outcomes. The findings underscore the importance of employing innovative teaching methods, such as environmental maps, to enhance students' understanding and engagement in the learning process.